Isavuconazole Prophylaxis in Patients With Hematologic Malignancies and Hematopoietic Cell Transplant Recipients. (8th April 2019) - Fontana, Lauren; Perlin, David S; Zhao, Yanan; Noble, Brie N; Lewis, James S; Strasfeld, Lynne; Hakki, Morgan
Abstract: Background: Isavuconazole (ISA) is an attractive candidate for primary mold-active prophylaxis in high-risk patients with hematologic malignancies or hematopoietic cell transplant (HCT) recipients. However, data supporting the use of ISA for primary prophylaxis in these patients are lacking. Methods: We conducted a retrospective review of breakthrough invasive fungal infections (bIFIs) among adult hematologic malignancy patients and HCT recipients who received ≥7 days of ISA primary prophylaxis between 1 September 2016 and 30 September 2018. The incidence of bIFIs in patients receiving ISA was compared to those receiving posaconazole (POS) and voriconazole (VOR) during the same time period. Results: One hundred forty-five patients received 197 courses of ISA prophylaxis. Twelve bIFIs ( Aspergillus fumigatus [5], Aspergillus species [2], Mucorales [2], Fusarium species [2], and Candida glabrata [1]) occurred, representing 8.3% of patients and 6.1% of courses, after a median duration of 14 days of ISA prophylaxis. All bIFIs occurred during periods of neutropenia. Seven patients (58.3%) died within 42 days of onset of bIFI. In addition, bIFIs complicated 10.2% of ISA, 4.1% of POS, and 1.1% of VOR courses among patients with de novo or relapsed/refractory acute myeloid leukemia during the study period, with invasive pulmonary aspergillosis (IPA) complicating 6.8% of ISA, 1.3% of POS, and zero VOR courses. Conclusions: Although ISA has been approved for treatment of invasive Aspergillus and mucormycosis, we observed an increased rate of bIFI, notably IPA, using ISA for primary prophylaxis. These results support the need for further study to determine the role of ISA as primary prophylaxis. Abstract : Isavuconazole primary prophylaxis in patients with hematologic malignancies and hematopoietic cell transplant recipients was associated with a greater-than-expected incidence of breakthrough invasive aspergillosis. Additional studies are needed to determine the role of isavuconazole as primary prophylaxis in these patient populations.